IN-MEMORY PARALLEL PROCESSING FOR MATRIX TRANSPOSE. - Malita, Mihaela; Ştefan, Gheorghe M. (InSight: Rivier Academic Journal)
Efficient implementation of parallel algorithms for matrix transposition requires careful consideration of data distribution, synchronization, communication overheads, and load balancing to achieve optimal performance in-memory parallel processing. We propose an algorithm and its implementation for execution on a p-cell parallel in-memory cellular processor (CP). Two versions of CP are considered, one with size in O(p) and another with size in O(p×log p).